The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1139/f96-335
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of density-dependent cohort splitting in age-0 yellow perch, (Perca flavescens): potential behavioural mechanisms and population-level consequences

Abstract: Two sequential cohorts of age-0 yellow perch (Perca flavescens), differing approximately threefold in density, were observed for their ontogeny of spatial distribution, growth, and diet in Lake St. George, Ontario. The lower density cohort exhibited typical ontogenetic spatial behaviour patterns consisting of an early pelagic phase followed by a complete migration to the littoral zone by midsummer. The high-density cohort appeared to split into a faster growing littoral component and a slower growing pelagic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 34 publications
3
42
2
Order By: Relevance
“…Nevertheless, low intake rate of rivals could be related to their lower social status retained from recent interactions, like it was observed in sticklebacks of different competitive rank (Milinski 1982). Our findings support the hypothesis that interference competition was the mechanism responsible for the density-dependent cohort splitting (Post et al 1997). The authors found that the high-density cohort of yellow perch, P. flavescens, split into a faster growing littoral component and a slower growing pelagic component.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, low intake rate of rivals could be related to their lower social status retained from recent interactions, like it was observed in sticklebacks of different competitive rank (Milinski 1982). Our findings support the hypothesis that interference competition was the mechanism responsible for the density-dependent cohort splitting (Post et al 1997). The authors found that the high-density cohort of yellow perch, P. flavescens, split into a faster growing littoral component and a slower growing pelagic component.…”
Section: Discussionsupporting
confidence: 84%
“…Such variation in body size is often thought to be related to interference competition and social hierarchy (Metcalfe et al 1989, Skulason & Smith 1995. Post et al (1997) suggested that interference competition for the littoral zone resource (both food and refuge from predators) could explain an aberrant habitat shift when a cohort was abundant. Westerberg et al (2004) observed aggression in experiments with small groups of 0+ perch, P. fluviatilis, but no proximate cues inducing aggressive interactions and establishment of social hierarchy among juvenile perch were found until now.…”
Section: Introductionmentioning
confidence: 99%
“…This diet shift resulted in a higher initial larval growth rate, and this early growth advantage was still detectable in the bimodal size distribution of larvae 30 days after peak hatch. Post et al (1997) observed a bimodality in the size structure of young perch cohorts in Lake St George, Ontario, in some years but not in others. They attributed this within-cohort size difference to density-dependent competition, but this splitting of a cohort into two size groups is also consistent with an early growth advantage for the part of the cohort that may be related to earlier onset of optimal feeding due to temporal differences in prey community composition.…”
Section: Implications Of Diet Shifts Across Systemsmentioning
confidence: 82%
“…Data on larval yellow perch diet composition, growth rates, TLs, and of abiotic variables (temperature and turbidity), prey availability (zooplankton prey densities, length and mass), competition (yellow perch larval densities) and predation (potential predator densities) from 2006 and 2008 were used as potential factors to develop the Lake Erie IBM and Statistical GLM. These environmental variables were considered because previous studies have found them to be related to larval fish foraging behavior and growth (Post and Prankevicius 1987;Post and McQueen 1988;Post and Johannes 1997;Power and van den Heuvel 1999;Pangle et al 2012). We also included day of year because it can be related to factors such as cumulative degree-days or number of days in which water temperature allowed for positive growth (Post and McQueen 1988) and/or a synchronization with their prey cycles (Wu and Culver 1994) both of which are more difficult to quantify.…”
Section: Methodsmentioning
confidence: 99%